Criminal Sanctions for Terrorism Perpetrators in the Perspective of Islamic Criminal Law : (Bali Bombing Case Study I) - Muhammad Arif Fattahillah; Noor Azizah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
When the crime of terrorism of the Bali bombing on October 12, 2002 occurred in Indonesia, which is not a country that applies Islamic law, then this became a problem among Muslims in Indonesia. it is clear that the behavior of terrorism is a form of Jarimah Al-Bagyu which sanctions in the form of Qisas and diyat, but in Indonesia there are perpetrators of terrorism who get the death penalty there are those who get life imprisonment with different sanctions sentenced by the judge. The research method used is normative juridical (legal research) which is descriptive analysis with primary data sourced from legal materials. The results of the research conclude that the perpetrators of the Bali I bombing terrorism in Islamic Criminal Law include indirect co-perpetrators (Isytirak ghairul mubasir/isytirak bittasabbubi) appropriately applied in the form of death penalty and life imprisonment. So that this paper will provide an overview of the perpetrators of indirect participation in which sanctions in Islamic criminal law are given in the form of Ta'zir, the judge's verdict in the Indonesian State against terrorism suspects is a form of Ta'zir, namely the punishment for the perpetrator of thejarimah is left entirely to the ruler or judge